Computer programming and robotics in basic education - Cabrera Delgado, José Manuel (Avances en Supervisión Educativa, 2015)
This article aims to get an overview of the process of including the computer programming and the robotics in the educational curriculum of the basic education in several European countries, including Spain. For this purpose, the cases of Estonia and England are briefly analyzed, two countries in the European Union which can be considered pioneers in implementing such teaching. Also, in relation to Spain, it is analyzed some of the current initiatives implemented by some Autonomous Communities in this sense.